Visual expressions of environmental care in primary school students’ drawings - Antosa, Zariul; Jupriani, Jupriani (UIN Raden Mas Said Surakarta, 2024)
This study analyzed primary school children's drawings from a drawing competition to explore their attitudes towards environmental care. Employing a descriptive qualitative approach, data collection was conducted through observation, interviews, and document analysis. Data analysis was performed using an interactive model analysis technique. The findings reveal that the drawings depict both school and living environments, featuring objects from children's daily activities. The drawings do not fit into a single category, but are a mix of organic, structural, schematic, expressionist, and literary types. The drawing objects were depicted naturally and proportionally using primary colors. The students' visual expressions predominantly used green, red, yellow, and brown, with minimal mixing. The way the drawings are expressed shows the children's personal expressions, but the choice of objects tends to be influenced by adult thinking. The contribution of teachers in developing children's cognitive and skill skills is evident in their drawings, as revealed by interviews with the children regarding the sources of their ideas. Drawing objects reflect children's attitudes, behaviors, and values regarding environmental care, illustrated through scenes such as playing in the schoolyard, family settings, playground objects, school activities, and natural environments. The shapes were naturalistic, simple, overlapping, reclining, and layered with no transparent objects. Their choice of objects and techniques was shaped by their knowledge and experience of nature, with each drawing outlined. Children use drawings to express life events and experiences, so teachers should value these drawings, as research often overlooks children's perspectives in favor of adult viewpoints.